Comparison of Contralateral Acceleromyography and Electromyography for Posttetanic Count Measurement. (15th December 2022) - Joo, Hyunyoung; Cho, Sooyoung; Lee, Jong Wha; Kim, Won Joong; Lee, Hyun Jung; Woo, Jae Hee; Lee, Giyear; Baik, Hee Jung
Abstract : Background: Electromyography has advantages over mechanomyography and acceleromyography. Previously, agreement of the train-of-four counts between acceleromyography and electromyography was found to be fair. The objective of this study was to assess the agreement of posttetanic count including agreement of neuromuscular blockade status (intense block, posttetanic count equal to 0; or deep block, posttetanic count 1 or greater and train-of-four count equal to 0) between acceleromyography and electromyography. Methods: Thirty-six patients, aged 20 to 65 yr, participated in this study. A dose of 0.6 mg/kg rocuronium, with additional dose of 0.3 mg/kg if required, was administered to the patients. The train-of-four and posttetanic counts were monitored in the contralateral arm using electromyography at the first dorsal interosseus or adductor pollicis, and acceleromyography at the adductor pollicis. Posttetanic count measurements were performed at 6-min intervals; the responses were recorded until the train-of-four count reached 1. The authors evaluated the agreement of degree of neuromuscular blockade (intense or deep block) and that of posttetanic count between acceleromyography and electromyography. Results: The authors analyzed 226 pairs of measurements. The percentage agreement indicating the same neuromuscular blockade status (intense or deep block) between acceleromyography and electromyography was 73%. Cohen's kappa coefficient value was 0.26. After excluding data with acceleromyography–posttetanic counts greater than 15, a total of 184 pairs of posttetanic counts were used to evaluate the agreement between the two monitoring methods. For acceleromyography–posttetanic count, 42 (23%) pairs had the same electromyography–posttetanic count, and 93 (50%) pairs had more than the electromyography–posttetanic count. The mean posttetanic count on electromyography was 38% (95% CI, 20 to 51%) lower than that on acceleromyography ( P = 0.0002). Conclusions: Acceleromyography frequently counted more twitches than electromyography in posttetanic count monitoring. Acceleromyography– and electromyography–posttetanic counts cannot be used interchangeably to assess the degree of neuromuscular blockade. Abstract : The agreement of posttetanic counts monitored in contralateral arms by acceleromyography and electromyography was determined in 35 patients given 0.6 mg/kg rocuronium after induction of anesthesia and calibration of the monitors, with additional doses of 0.3 mg/kg if required. Seventy-three percent of 226 pairs of acceleromyography– and electromyography–posttetanic count measurements indicated the same neuromuscular blockade status (intense or deep block). Of 184 pairs of posttetanic counts of 15 or less, 42 (23%) acceleromyography–posttetanic counts were equal to electromyography–posttetanic counts, 93 (50%) were more than electromyography counts, and 49 (27%) were less than electromyography counts.